Estrogen Receptor Inhibits Mineralocorticoid Receptor Transcriptional Regulatory Function - Barrett Mueller, Katelee (Endocrine Society, 2014)
The steroid hormone aldosterone (aldo) contributes to cardiovascular disease in animal models and in humans. Aldo activates the mineralocorticoid receptor (MR), a hormone-activated transcription factor, and indeed, pharmacological MR inhibition improves cardiovascular outcomes. Because the incidence of cardiovascular disease is lower in premenopausal women, we hypothesized that estrogen (E2) signaling through the estrogen receptor (ER) may protect the vasculature by inhibiting the detrimental effects of aldo signaling through the MR. We demonstrate that E2-activated ER inhibits MR-mediated gene transcription from the mouse mammary tumor virus reporter in human embryonic kidney-293 cells. In contrast, aldo-activated MR does not affect ER-mediated gene transcription. The ERα N terminus (amino acids 1–253) containing part of the DNA-binding domain is sufficient to inhibit MR genomic function, although point mutations reveal that DNA binding, ligand-independent activation, and rapid nongenomic ERα signaling are not required for this effect. Furthermore, ERα and MR are part of a complex in cell lysates, with amino acids 1–233 of the ERα N terminus being sufficient to complex with the MR. Overall, the ability of ERα to inhibit MR-mediated gene transcription correlates with the ability of ERα segments to both localize to the nucleus and complex with the MR. In cultured vascular endothelial cells expressing ERα, E2 inhibits aldo induction of the vascular MR target gene intercellular adhesion molecule-1 (ICAM-1). ICAM-1 induction by endothelial MR is known to promote vascular inflammation that could contribute to the mechanism of aldo-induced atherosclerosis. E2 also inhibits aldo induction of ICAM-1 protein and prevents aldo-enhanced leukocyte adhesion to endothelial cells. These studies support a new model in which E2-activated ER in endothelial cells forms a complex with MR in the nucleus to modulate MR regulation of the proinflammatory gene ICAM-1. Estrogen inhibition of MR regulation of genes that contribute to cardiovascular disease may be a new mechanism by which premenopausal women are protected from cardiovascular disease.